THE FINANCIAL STATEMENTS FOR THE ENTERPRISE MANAGEMENT - N. Morgun; O. D’Yakonova (Вестник университета, 2019)
This article discusses the importance of accounting (financial) statements in the process of management of financial resources. A review of financial indexes calculated on the basis of the financial statements and used for enterprise management is presented.